Managerial Strategy of Buton District Hospital to Maintain Type C Hospital Status - Kathrine, Anita Septiana Maria; Syaodih, Erliany; Veranita, Mira (International Journal Administration, Business & Organization, 2025)
Hospitals must develop relevant business strategies in order to compete. In determining a strategy, internal and external analysis is needed so that the strategy used is appropriate. Based on a survey by the Provincial Health Service, several criteria for type C hospitals were not met, so the Buton Regency Regional Hospital was threatened with being downgraded. This research aims to determine the appropriate management strategy for District Hospitals in HR management, hospital facilities, and financial management to maintain type C class status. This qualitative study uses an in-depth interview method with purposive sampling. The sample in this study was the regional secretary as the representative of the regional government as the owner of the hospital, the hospital director, the head of finance, the head of personnel, the head of hospital facilities, general practitioners, and specialist doctors of all divisions in the hospital, the head nurse of each treatment room. The research using SWOT analysis results shows that Buton District Hospital is in a position of growth and development and, based on the internal-external matrix, is in a stable position. This condition is good because Buton District Hospital is in a favorable position to take advantage of existing opportunities and strengths. The implications of the research results are for the management of Buton District Hospital to be used as suggestions or references for consideration in making hospital strategies to maintain the status of a type C hospital. Providing input to the head of the Regional Government regarding the great need for financial assistance to meet the requirements of the Minister of Health Regulation regarding the requirements for a type C hospital that Buton District Hospital has not met.